Cost-effectiveness analysis of the human recombinant epidermal growth factor in the management of patients with diabetic foot ulcers. Issue 1 (1st January 2018) - Romero Prada, Martin; Roa, Carolina; Alfonso, Pamela; Acero, German; Huérfano, Lina; Vivas-Consuelo, David
ABSTRACT: Introduction : Diabetic foot ulcers are one of the most frequent complications of diabetes; such ulcers cause an increase in the costs of the health care of the diabetic patient and can even cause disability due to amputation in the patient. Although a proportion of patients achieve a spontaneous closure of ulcers, others require medical or surgical treatment. Objective : To determine the cost-effectiveness of the intra- and perilesional application of recombinant human epidermal growth factor (rhEGF), as opposed to conventional therapy for the management of patients diagnosed with Wagner's 3 or 4 diabetic foot ulcer in Colombia. Methodology : Using a Markov model, the process of care of a diabetic patient with diagnosis of Wagner's 3 or 4 ulcer receiving conventional treatment, or intra- and perilesional rhEGF, is configured. The evaluation cycles of the treatments are weekly over a 5-year horizon and the outcomes evaluated are quality-adjusted life years (QALYs) and the number of amputations avoided by each treatment scheme, in addition to the total costs for treatments. Results : For the analysed base case, in the outcome of amputations, it was found that the factor presents 39 fewer amputations, in a cohort of 100 patients, compared with conventional treatment. Likewise, QALYs are 0.65 more with the use of rhEGF in an average patient. The estimated cost-utility ratio for the base case would be below the threshold established for Colombia. Conclusions : The intra- and perilesional application of rhEGF is a more effective therapeutic option than conventional therapy in the treatment of patients with Wagner's 3 or 4 diabetic foot ulcers and is cost-effective, taking as an outcome the QALYs for Colombia from the perspective of the health system.